Perancangan Self-assessment ISO 22000:2018 dengan Metode Baldrige Scoring di PT. Alam Jaya Seafood - Jeremy Kusuma; Jani Rahardjo (Jurnal Titra, 2022)
Competition in the era of globalization is inevitable and companies are racing to improve themselves continuously. PT. Alam Jaya Seafood wants to measure their ISO 22000:2018 standards implementation readiness. PT. Alam Jaya Seafood is HACCP certified, but not ISO 22000:2018 certified. Internal audit is a way to measure the implementation readiness of the food safety management system as well as a requirement to obtain ISO 22000:2018 certification. Self-assessment can be carried out on an internal audit of ISO 22000:2018 by the company. The assessment criteria used is the Baldrige scoring method. The Baldrige scoring method is centered on the ADLI criteria (Approach, Deployment, Learning, and Integration). The output of the research is the ISO 22000:2018 self-assessment design which consists of questions and assessment degradation and self-assessment implementation instructions. The purpose of creating the self-assessment design is to create an independent and measured way of assessing ISO 22000:2018 food safety management system in PT. Alam Jaya Seafood.